ANALYZING OF WEB-BLOG MEDIA IN LEARNING MATHEMATICS ON POST PANDEMIC COVID-19 - Simangunsong, Alfauzan Ramadhanny; Irvan, Irvan (UIN Sumatera Utara Medan, 2023)
Pandemic has brought everyone to the highest climax in the development of learning innovations, including digital learning. The popularity of web digital learning applications and pages, video conferencing, digital quizzes, to audio-visual-based learning tools has brought civilization to various forms of learning. This study aims to analyze the implementation of the use of web-blog-based digital learning media in mathematics learning in junior high schools. This research was conducted in the first week of March 2023. This research used a qualitative method, with data collection techniques in the form of observation, interviews, and documentation studies. The researcher in this case functions as the main tool for collecting data with the main data collection techniques through interviews, explanations and documentation. The results of the analysis in research on the use of web-blogs in learning mathematics show that there is ease in strengthening concept understanding, learning that is flexible and can be accessed repeatedly, the time for giving material and assignments is concise, and motivating the use of gadgets positively. Other results show obstacles in the form of resource capabilities that have not been maximized, minimal availability of devices, limited internet access based on region and economic capacity, to limited abilities of students and educators in using digital media. The analysis above provides a description to educators in terms of selecting learning media when analyzing material in the preparation of lesson implementation plans, so that the use of web-blog media can be adjusted and varied according to resources and learning needs.